Nutritional and bioactivity properties of selected earthworm species for potential cosmeceutical applications - Azmi, Nurhazirah (2013)
Earthworms are invertebrates that have been widely applied to environmental and land study, however, a new chapter opens opportunities of research in cosmetic and medicine. The objectives of the experiment were to evaluate the nutritional and antioxidant properties from the earthworms Eudrilus eugeniae, Eisenia fetida and Lumbricus rubellus and to examine the bioactivity properties of the earthworms extract in tyrosinase, matrix metalloproteinase-1, and elastase inhibitory activities for cosmeceutical applications. The analyzed components include moisture, available carbohydrates, total lipids, dietary fiber, crude protein, amino acids, ash, and minerals. The amino acids profile of the earthworm extracts was evaluated using High Performance Liquid Chromatography (HPLC). Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-Page) was used to determine and separate the protein based on size. The results showed E. fetida had slightly higher amount of protein and ash than L. rubellus and E. euginae. All the earthworm extracts showed high amounts of minerals ranging from 3-22% in calcium, potassium and phosphorus. All the extracts had the least amount of the amino acid cysteine, ranging from 0.17-0.21 mg/100 g protein, while the highest concentration is leucine, being 1.0-2.5 mg/100 g protein. Lysine and methionine, which were the limiting amino acids in most feedstuff, were present in all the extracts, ranging from 0.29-1.16 mg/100 g proteins and 0.3-0.57 mg/100 g protein, respectively. Molecular weights of earthworm extracts showed from 13-430 kDa under the optimal conditions of sodium dodecyl sulphatepolyacrylamide gel electrophoresis (SDS-Page). E. fetida exhibited wide molecular weight distribution compared to L. rubellus and E. eugeniae which consisted of 11, 10 and 6 prominent bands, respectively. In addition, E. fetida had the highest antioxidant activity (91.76%) using 2,2-diphenyl-1-picrylhydracyl (DPPH) assay compared to E. eugeniae and L. rubellus. At 25 mg/ml concentration, the antioxidant activity of E. fetida using DPPH assay was almost comparable to ascorbic acid (10mg/ml) which is usually used as antioxidant in most pharmaceutical products. All extracts demonstrated excellent inhibitory effects on tyrosinase. Extract from E. fetida gave the highest tyrosinase inhibition activity (80.12%) compared to L. rubellus (72.02%) and E. eugeniae (71.28%). However, their inhibition was still lower than the standard L-cysteine. In conclusion, this study provides nutritional compositional of earthworms as well as new findings on bioactivity properties having antioxidant, anti-tyrosinase and anti-aging properties. All the earthworms demonstrated valuable properties in antioxidant, anti-aging and whitening inhibition capacity despite the species. As such, it can be a potential candidate for application and utilization in cosmeceutical products.